A mix proportion design method of steel slag doped recycled asphalt concrete

CN117877637BActive Publication Date: 2026-10-13WUHAN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311784416.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2026-10-13
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

[0004]本发明针对以上技术问题,充分考虑钢渣吸水率高、RAP难以分散的特性,提出了一种掺钢渣再生沥青混凝土的配合比设计方法,解决目前以钢渣和回收沥青路面制备沥青混凝土时出现最大理论密度计算不准确,配合比设计无法贴近实际工况的问题

Benefits of technology

[0032]本发明充分考虑钢渣吸水率高、RAP难以分散的特性,提出了一种掺钢渣再生沥青混凝土的配合比设计方法,可以较为准确的提供矿料级配和最大理论相对密度两个关键参数的试验方法,使配合比设计结果更加贴近工程实际情况,可为高吸水率固体废弃物及沥青再生技术提供一定的技术参考。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117877637B_ABST
    Figure CN117877637B_ABST
Patent Text Reader

Abstract

The application discloses a mixing proportion design method of steel slag doped recycled asphalt concrete. The application fully considers the characteristics of high water absorption of steel slag and difficulty of dispersion of RAP, adopts the same asphalt as the relative object in the mixing proportion design, measures the apparent relative density of the steel slag, determines the modified grading of the RAP, and regards the asphalt existing in the RAP as a part of the oil stone ratio to participate in the calculation of the maximum theoretical density, so that the test method of two key parameters of the mineral aggregate grading and the maximum theoretical relative density can be accurately provided, the volume index of the asphalt concrete can be accurately calculated, the best oil stone ratio is determined, the mixing proportion design result is closer to the engineering actual situation, and certain technical reference can be provided for the high water absorption solid waste and the asphalt recycling technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of road engineering materials technology, specifically relating to a mix design method for recycled asphalt concrete with steel slag. Background Technology

[0002] Mix design of asphalt concrete is a crucial step in asphalt pavement construction, ensuring its optimal performance during service. With the development of transportation, solid waste materials, such as steel slag, and recycled asphalt pavement (RAP) are increasingly being used in the preparation of asphalt concrete.

[0003] However, existing mix design methods cannot adequately adapt to the material properties of steel slag and recycled asphalt pavement (RAP). Specifically, the main technical problems include: (1) Steel slag has a high water absorption rate, generally between 1.7% and 2.5%. Under high water absorption conditions, the formula recommended by the standard cannot accurately calculate the amount of asphalt absorbed by the steel slag, which reduces the accuracy of the effective relative density of the aggregate and further affects the accuracy of the calculation of the maximum theoretical density and the porosity of the mixture. (2) RAP is recycled asphalt pavement, which is composed of aggregates wrapped with asphalt. The aggregates are bonded by the asphalt into particles of different sizes. In the gradation fitting process, RAP is generally dried and then directly screened or RAP is burned to remove the asphalt before screening. However, during the mixing process of RAP, the various aggregate particles are difficult to completely disperse under the bonding effect of asphalt. Therefore, neither direct screening nor screening after burning can accurately reflect the true gradation of RAP. (3) RAP density measurement: Since RAP is a particle of asphalt-coated aggregate, it contains many small voids. During the density measurement process, the RAP density will deviate significantly from the actual density, which will further affect the accuracy of the calculation of the maximum theoretical density and the void ratio of the mixture. Summary of the Invention

[0004] To address the above-mentioned technical problems, this invention fully considers the characteristics of high water absorption rate of steel slag and difficulty in dispersing RAP, and proposes a mix design method for recycled asphalt concrete with steel slag. This solves the problem that the maximum theoretical density calculation is inaccurate and the mix design cannot closely reflect actual working conditions when preparing asphalt concrete with steel slag and recycled asphalt pavement.

[0005] The technical solution of the present invention is implemented in the following manner:

[0006] A mix design method for recycled asphalt concrete with steel slag, comprising the following steps:

[0007] S1. Utilize steel slag gradation, RAP gradation, and mineral powder gradation, combined with industry gradation range standards, to determine the aggregate gradation of recycled asphalt concrete with steel slag.

[0008] S2. Determine the asphalt-aggregate ratio for recycled asphalt concrete with steel slag;

[0009] S3. Based on the apparent relative density of steel slag, the effective relative density of RAP, the relative density of mineral powder, the relative density of asphalt, and the proposed asphalt-aggregate ratio, the maximum theoretical relative density of recycled asphalt concrete with steel slag is calculated; the formula for calculating the maximum theoretical relative density of recycled asphalt concrete with steel slag is:

[0010]

[0011] In the formula, γ ti γ is the maximum theoretical relative density, γ1 is the apparent relative density of the steel slag, and γ se γ is the effective relative density of RAP. c γ represents the relative density of the mineral powder. a P is the relative density of the asphalt used. a The proposed oil-stone ratio;

[0012] S4. Based on the aggregate gradation of the recycled asphalt concrete with steel slag and the proposed asphalt-aggregate ratio, Marshall tests were conducted to determine the bulk density of Marshall specimens under different asphalt-aggregate ratios. Based on the maximum theoretical relative density of the recycled asphalt concrete with steel slag, the porosity of the asphalt concrete with steel slag under each asphalt-aggregate ratio was calculated.

[0013] S5. The optimal oil-stone ratio is the oil-stone ratio corresponding to a porosity of 4.0%.

[0014] S6. Test the basic performance of recycled asphalt concrete with steel slag under the optimal asphalt-aggregate ratio and obtain the basic performance data.

[0015] If the basic performance data meets the standard requirements, the optimal asphalt-aggregate ratio is used as the optimal mix proportion for the steel slag recycled asphalt concrete. If the basic performance data does not meet the requirements, asphalt admixtures are added, and the basic performance is retested until the basic performance data meets the standard requirements. The optimal asphalt-aggregate ratio and the amount of asphalt admixture added are then used as the optimal mix proportion for the steel slag recycled asphalt concrete.

[0016] Preferably, in step S1, the RAP gradation is a modified gradation of RAP, and the determination method includes: uniformly dividing the RAP into two parts, drying one part to constant weight, and then sieving it to obtain the first gradation P. ai Another portion was subjected to combustion treatment, and the resulting RAP was sieved to obtain the second-grade P. bi Then use formula P Ri =θP ai +(1-θ)P bi The corrected gradation of RAP is obtained.

[0017] Preferably, in the formula for calculating the corrected gradation of RAP, the correction coefficient θ ranges from 0.1 to 0.4.

[0018] Preferably, the particle size of RAP is ≤10mm.

[0019] Preferably, in step S3, the effective density of RAP is determined by: subjecting the RAP to combustion treatment, and calculating the effective relative density of the RAP based on the apparent relative density and the bulk relative density of the RAP after combustion; the formula for calculating the effective relative density of RAP is as follows:

[0020] C = 0.033W x 2 -0.2936W x +0.9339

[0021] γ se =C×γ sa +(1-C)×γ sb

[0022] In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x This represents the water absorption rate of RAP after combustion.

[0023] Preferably, in step S3, the apparent relative density of the steel slag is determined using the basket method.

[0024] Preferably, in step S2, the asphalt-aggregate ratio is the mass percentage of asphalt to aggregate, and the asphalt includes the asphalt in the RAP and the asphalt to be added.

[0025] Preferably, in step S4, the formula for calculating the porosity of steel slag-mixed asphalt concrete is:

[0026]

[0027] In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. f The bulk density of the specimen is given.

[0028] Preferably, in step S5, if there is no asphalt-aggregate ratio that exactly corresponds to a void ratio of 4.0%, it is determined by interpolation; if the void ratio of the mixture corresponding to different asphalt-aggregate ratios does not cover 4.0%, the range of the asphalt-aggregate ratios proposed in step S2 is expanded until the void ratio of the mixture covers 4.0%.

[0029] Preferably, in step S6, the asphalt admixture includes one or more of petroleum resin, aromatic oil, SBS, and epoxy resin, and the dosage is 1 to 9% of the mass of asphalt in the mixture.

[0030] Preferably, in step S6, the basic performance data includes Marshall stability, water immersion residual stability, low-temperature bending failure strain, and dynamic stability data.

[0031] The beneficial effects of this invention are:

[0032] This invention fully considers the characteristics of high water absorption rate of steel slag and difficulty in dispersing RAP, and proposes a mix design method for recycled asphalt concrete with steel slag. It can provide experimental methods for two key parameters, aggregate gradation and maximum theoretical relative density, which can make the mix design results closer to the actual engineering situation and provide certain technical references for high water absorption solid waste and asphalt recycling technology. Attached Figure Description

[0033] Figure 1 This is a flowchart of a mix design method for recycled asphalt concrete with steel slag according to the present invention. Detailed Implementation

[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0035] Steel slag-infused recycled asphalt concrete is composed of steel slag, recycled asphalt pavement (RAP), asphalt, and mineral powder. This invention provides a mix design method for steel slag-infused recycled asphalt concrete, taking into full account the problems of RAP dispersion, RAP density, and high water absorption rate of steel slag under actual engineering conditions.

[0036] like Figure 1 As shown in the figure, the mix design method for recycled asphalt concrete with steel slag provided in this embodiment of the invention includes the following steps:

[0037] S1. Using steel slag gradation, RAP gradation, and mineral powder gradation, and in conjunction with industry gradation range standards, determine the aggregate gradation for recycled asphalt concrete with steel slag; wherein, the RAP gradation is a modified RAP gradation, and the determination method includes: uniformly dividing RAP into two parts, drying one part to constant weight, and then sieving it to obtain the first gradation P. ai Another portion was subjected to combustion treatment, and the resulting RAP was sieved to obtain the second-grade P. bi Then use formula P Ri =θPai +(1-θ)P bi The corrected gradation of RAP is obtained. Preferably, the particle size of RAP is ≤10mm, and the correction coefficient θ ranges from 0.1 to 0.4.

[0038] S2. Determine the asphalt-aggregate ratio of the asphalt mixture; the asphalt-aggregate ratio is the mass percentage of asphalt to aggregate, and the asphalt includes the asphalt in the RAP and the asphalt to be added.

[0039] S3. The apparent relative density of steel slag is determined by the basket method. Specifically, the basket method is the method provided by T0304-2005. The difference is that when determining the apparent relative density of steel slag, the water used in T0304-2005 is replaced with asphalt. The test temperature of the asphalt is 160℃~170℃, and the temperature of the steel slag is 190℃. The type of asphalt is consistent with the asphalt used in the mix design.

[0040] Determining the effective relative density of RAP: The RAP is subjected to combustion treatment. Based on the apparent relative density and bulk relative density of the RAP after combustion, the effective relative density of the RAP is calculated. The calculation formula is as follows:

[0041] C = 0.033W x 2 -0.2936W x +0.9339

[0042] γ se =C×γ sa +(1-C)×γ sb

[0043] In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x This represents the water absorption rate of RAP after combustion.

[0044] Based on the apparent relative density of steel slag, the effective relative density of RAP, the relative density of mineral powder, the relative density of asphalt, and the proposed asphalt-aggregate ratio, the maximum theoretical relative density of recycled asphalt concrete with steel slag is calculated. The formula for calculating the maximum theoretical relative density of recycled asphalt concrete with steel slag is as follows:

[0045]

[0046] In the formula, γ ti γ is the maximum theoretical relative density, γ1 is the apparent relative density of the steel slag, and γ se γ is the effective relative density of RAP. cγ represents the relative density of the mineral powder. a P is the relative density of the asphalt used. a The proposed oil-stone ratio;

[0047] S4. Based on the aggregate gradation and the proposed asphalt-aggregate ratio, conduct Marshall tests to determine the bulk density of Marshall specimens at different asphalt-aggregate ratios. Then, based on the maximum theoretical relative density of recycled asphalt concrete, calculate the porosity of the mixture at each asphalt-aggregate ratio. The formula for calculating the porosity of the mixture is:

[0048]

[0049] In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. f The bulk density of the specimen is given.

[0050] S5. The optimal oil-aggregate ratio is the oil-aggregate ratio corresponding to a void ratio of 4.0%. If there is no oil-aggregate ratio that exactly corresponds to a void ratio of 4.0%, it is determined by interpolation. If the void ratio of the mixture corresponding to different oil-aggregate ratios does not cover 4.0%, the range of the oil-aggregate ratios determined in step S2 is expanded until the void ratio of the mixture covers 4.0%.

[0051] S6. Test the basic performance of recycled asphalt concrete with steel slag under the optimal asphalt-aggregate ratio and obtain the basic performance data.

[0052] If the basic performance data meets the standard requirements, the optimal asphalt-aggregate ratio is taken as the optimal composition of the steel slag-infused recycled asphalt concrete; if it does not meet the requirements, asphalt admixtures are added, and the basic performance is retested until the basic performance data meets the standard requirements. The optimal asphalt-aggregate ratio and the amount of asphalt admixture added are taken as the optimal composition of the steel slag-infused recycled asphalt concrete.

[0053] This invention omits the existing method of measuring the apparent relative density and bulk relative density of steel slag relative to water, and then estimating the effective relative density based on these values. Instead, it directly uses asphalt, identical to the mix design, as the relative medium to measure the apparent relative density of the steel slag. The resulting apparent relative density is the density of the steel slag after absorbing a certain amount of asphalt, and is numerically equal to its effective relative density. This change eliminates the need to estimate the asphalt absorption coefficient, directly reflecting the absorption of asphalt by the steel slag, resulting in more accurate results.

[0054] Currently, RAP (Rich Asphalt Acrylic Acid) is typically treated as a whole, with its density measured directly. However, RAP contains many small voids, leading to significant errors in density measurements. Furthermore, the asphalt in RAP undergoes re-fusion with aggregates and new asphalt during mixing. Therefore, this invention proposes a combustion method. First, the aggregates and asphalt in the RAP are separated. Then, the apparent relative density, bulk relative density, and water absorption rate of the RAP aggregates after combustion are measured. Due to the low water absorption rate of the aggregates in RAP, the effective relative density of the aggregates after combustion can be calculated more accurately using relevant formulas. The asphalt present in the RAP is included as part of the asphalt-aggregate ratio in the calculation of the maximum theoretical density. This comprehensive processing results in a more accurate proportion of RAP in the asphalt mixture by volume, and also improves the accuracy of the maximum theoretical density calculation.

[0055] Recycled asphalt (RAP) is typically obtained from milled old pavements. During its use, RAP needs to be sieved and graded into multiple sizes according to particle size before application. The particle size varies considerably depending on the source of the RAP, especially between direct sieving and post-combustion sieving. This invention crushes all RAP before use, standardizing it to a particle size ≤10mm. This eliminates the need for multiple gradation adjustments later due to differences in RAP size or origin. Furthermore, crushing reduces large particles in the RAP to smaller ones, preventing them from bearing excessive structural load in the recycled asphalt mixture. Larger RAP particles have poorer aggregate properties than newer aggregates, and bearing structural loads negatively impacts the strength and durability of the mixture.

[0056] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be described in more detail below with reference to the accompanying drawings.

[0057] Example 1

[0058] (1) Determine the gradation and apparent relative density of steel slag.

[0059] Steel slag with a particle size of 4.75–13.2 mm was screened to obtain the slag gradation, i.e., the passing rate P of each sieve opening. gi The results are shown in Table 1. The apparent relative density γ1 of the steel slag was then determined using the basket method to be 3.324 g / cm³. 3 .

[0060] Table 1. Screening Results of Steel Slag

[0061] <![CDATA[Pass rate P gi / %]]> 95.4 59.4 14.0

[0062] The basket method described above is the method provided by T0304-2005. The difference is that the water used in T0304-2005 is replaced with asphalt, the test temperature of the asphalt is 165℃, and the asphalt is ID modified asphalt.

[0063] (2) Determine the gradation of RAP

[0064] All recycled asphalt pavement RAP was crushed in a crusher to obtain waste asphalt mixture with a particle size ≤10mm. The crushed RAP was then evenly divided into two parts. One part was dried at 60-70℃ to constant weight and then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture. ai Another sample was processed using the combustion furnace method (the method provided in T0735-2011) to obtain the burned RAP and the asphalt content B1 = 5.7% in the RAP. The burned RAP was then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture. bi Using formula P Ri =θP ai +(1-θ)P bi With θ = 0.2, the corrected gradation of RAP is obtained, which is the throughput P per sieve aperture. i (See Table 2).

[0065] Table 2 Corrected Gradation of RAP

[0066]

[0067] (3) Determine the aggregate gradation of recycled asphalt concrete with steel slag

[0068] The mineral powder is sieved to obtain its gradation, i.e., the passing rate P of each sieve opening. ki (See Table 3). Utilizing steel slag gradation P gi , RAP gradation P i The gradation Pki of the mineral powder was determined by using the gradation range provided in Table 5.3.2-2 of JTG F40-2004 "Technical Specification for Construction of Asphalt Pavement on Highways" as a reference range for synthetic gradation fitting. This resulted in the synthetic aggregate gradation P after steel slag, RAP, and mineral powder were mixed in different mass ratios. Hi (See Table 4) Within the reference gradation range, the mass ratios of steel slag, RAP, and mineral powder are A = 11%, B = 88%, and C = 1%. Among them, the mass of RAP is the mass of RAP without bitumen, that is, the mass of RAP multiplied by (1-B1), and B1 is the bitumen content in RAP measured in step (2).

[0069] Table 3. Gradation of mineral powder

[0070] <![CDATA[Pass rate P ki / %]]> 100 98.7 84.5

[0071] Table 4 Aggregate gradation of recycled asphalt concrete with steel slag

[0072]

[0073] (4) Determine the asphalt-aggregate ratio of the asphalt mixture.

[0074] Using the aggregate gradation determined in step (3), four asphalt-aggregate ratios of 4.8%, 5.0%, 5.2%, and 5.4% were designed at intervals of 0.2%. The asphalt included asphalt in RAP and added ID modified asphalt.

[0075] (5) Determine the maximum theoretical relative density of recycled asphalt concrete with steel slag.

[0076] The apparent relative density γ of the RAP after combustion in step (2) was measured using the methods provided in T0304-2005 and T0330-2005. sa =2.735g / cm 3 The relative volume density γ of RAP after combustion sb =2.691g / cm 3 and water absorption rate W x =0.6%, the effective relative density γ of RAP was calculated. se =2.725g / cm 3 The calculation formula is as follows:

[0077] C = 0.033W x 2 -0.2936W x +0.9339

[0078] γ se =C×γ sa +(1-C)×γ sb

[0079] In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x This represents the water absorption rate of RAP after combustion.

[0080] Based on the apparent relative density γ1 of steel slag, which is 3.324 g / cm³,... 3 The effective relative density γ of RAP se =2.725g / cm 3 The relative density γ of mineral powder c= 2.695g / cm 3 The relative density γ of asphalt a= 1.025g / cm3 And the proposed oil-stone ratio P a The maximum theoretical relative density γ of recycled asphalt concrete with steel slag was calculated. ti The formula for calculating the maximum theoretical relative density of recycled asphalt concrete mixed with steel slag is:

[0081]

[0082] (6) Determine the porosity

[0083] Marshall tests were conducted based on the aggregate gradation and the proposed asphalt-aggregate ratio to determine the bulk density of Marshall specimens under different asphalt-aggregate ratios. Based on the maximum theoretical relative density of recycled asphalt concrete obtained in step (5), the porosity of the mixture under each asphalt-aggregate ratio was calculated. The relationship between the asphalt-aggregate ratio and porosity is shown in Table 5. The formula for calculating the porosity of the mixture is:

[0084]

[0085] In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. f The bulk density of the specimen is given.

[0086] Table 5 Relationship between oil-aggregate ratio and porosity

[0087] Porosity / % 4.9 4.2 3.8 3.2

[0088] The optimal oil-aggregate ratio is determined by interpolation based on a porosity of 4.0%. Table 5 shows that the optimal oil-aggregate ratio is 5.1%.

[0089] (7) Performance testing of recycled asphalt concrete with steel slag

[0090] Marshall specimens were prepared according to the gradation and optimal asphalt-aggregate ratio determined by the above steps. The Marshall stability, water immersion residual stability, low-temperature bending failure strain and dynamic stability of the concrete specimens were tested. The test results are shown in Table 6.

[0091] Table 6 Performance of Recycled Asphalt Concrete with Steel Slag

[0092]

[0093] Table 6 shows that the residual stability after immersion and the low-temperature flexural failure strain do not meet the requirements. Therefore, under the determined gradation and optimal asphalt-aggregate ratio, 2% of No. 150 aromatic oil (by weight of asphalt) and 1% of E51 epoxy resin (by weight of asphalt) were added to prepare new Marshall specimens, and their properties were tested. The test results are shown in Table 7. Table 7 shows that all properties meet the requirements, and the mix proportion verification is qualified. Therefore, an asphalt-aggregate ratio of 5.1%, 2% of No. 150 aromatic oil (by weight of asphalt), and 1% of E51 epoxy resin (by weight of asphalt) were selected as the mix composition for the steel slag recycled asphalt concrete.

[0094] Table 7 Performance of Recycled Asphalt Concrete with Steel Slag

[0095]

[0096] Example 2

[0097] (1) Determine the gradation and apparent relative density of steel slag.

[0098] Steel slag with a particle size of 4.75–13.2 mm was screened to obtain the slag gradation, i.e., the passing rate P of each sieve opening. gi The results are shown in Table 8. The apparent relative density γ1 of the steel slag was then determined using the basket method to be 3.248 g / cm³. 3 .

[0099] Table 8. Screening Results of Steel Slag

[0100] <![CDATA[Pass rate P gi / %]]> 87.5 43.8 0.2

[0101] The basket method described above is the method provided by T0304-2005. The difference is that the water used in T0304-2005 is replaced with asphalt, the test temperature of the asphalt is 165℃, and the asphalt is ID modified asphalt.

[0102] (2) Determine the gradation of RAP

[0103] All recycled asphalt pavement RAP was crushed in a crusher to obtain waste asphalt mixture with a particle size ≤10mm. The crushed RAP was then evenly divided into two parts. One part was dried at 60-70℃ to constant weight and then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture. ai Another sample was processed using the combustion furnace method (the method provided in T0735-2011) to obtain the burned RAP and the asphalt content B1 = 6.1% in the RAP. The burned RAP was then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture. bi Using formula P Ri =θP ai +(1-θ)P bi With θ = 0.25, the corrected gradation of RAP is obtained, which is the throughput P per sieve aperture.i (See Table 9).

[0104] Table 9 RAP's Modified Gradation

[0105]

[0106] (3) Determine the aggregate gradation of recycled asphalt concrete with steel slag

[0107] The mineral powder is sieved to obtain its gradation, i.e., the passing rate P of each sieve opening. ki (See Table 10). Utilizing steel slag gradation P gi , RAP gradation P i The gradation Pki of the mineral powder was determined by using the gradation range provided in Table 5.3.2-2 of JTG F40-2004 "Technical Specification for Construction of Asphalt Pavement on Highways" as a reference range for synthetic gradation fitting. This resulted in the synthetic aggregate gradation P after steel slag, RAP, and mineral powder were mixed in different mass ratios. Hi (See Table 11) Within the reference gradation range, the mass ratios of steel slag, RAP, and mineral powder are A = 38%, B = 61%, and C = 1%. Among them, the mass of RAP is the mass of RAP without bitumen, that is, the mass of RAP multiplied by (1-B1), and B1 is the bitumen content in RAP measured in step (2).

[0108] Table 10. Gradation of mineral powder

[0109] <![CDATA[Pass rate P ki / %]]> 100 100 94.5

[0110] Table 11 Aggregate gradation of recycled asphalt concrete with steel slag

[0111]

[0112] (4) Determine the asphalt-aggregate ratio of the asphalt mixture.

[0113] Using the aggregate gradation determined in step (3), four asphalt-aggregate ratios of 4.5%, 4.7%, 4.9%, and 5.1% were designed at intervals of 0.2%. The asphalt included asphalt in RAP and added ID modified asphalt.

[0114] (5) Determine the maximum theoretical relative density of recycled asphalt concrete with steel slag.

[0115] The apparent relative density γ of the RAP after combustion in step (2) was measured using the methods provided in T0304-2005 and T0330-2005. sa =2.912g / cm 3 The relative volume density γ of RAP after combustion sb =2.846g / cm 3 and water absorption rate Wx =0.8%, the effective relative density γ of RAP was calculated. se =2.894g / cm 3 The calculation formula is as follows:

[0116] C = 0.033W x 2 -0.2936W x +0.9339

[0117] γ se =C×γ sa +(1-C)×γ sb

[0118] In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x This represents the water absorption rate of RAP after combustion.

[0119] Based on the apparent relative density γ1 of steel slag, which is 3.248 g / cm³,... 3 The effective relative density γ of RAP se =2.894g / cm 3 The relative density γ of mineral powder c= 2.653 g / cm³ 3 The relative density γ of asphalt a= 1.025g / cm 3 And the proposed oil-stone ratio P a The maximum theoretical relative density γ of recycled asphalt concrete with steel slag was calculated. ti The formula for calculating the maximum theoretical relative density of recycled asphalt concrete mixed with steel slag is:

[0120]

[0121] (6) Determine the porosity

[0122] Marshall tests were conducted based on the aggregate gradation and the proposed asphalt-aggregate ratio to determine the bulk density of Marshall specimens under different asphalt-aggregate ratios. Based on the maximum theoretical relative density of recycled asphalt concrete obtained in step (5), the porosity of the mixture under each asphalt-aggregate ratio was calculated. The relationship between the asphalt-aggregate ratio and porosity is shown in Table 12. The formula for calculating the porosity of the mixture is:

[0123]

[0124] In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. fThe bulk density of the specimen is given.

[0125] Table 12 Relationship between oil-aggregate ratio and porosity

[0126] Porosity / % 5.1 4.3 4.0 3.5

[0127] The optimal oil-stone ratio is defined as the oil-stone ratio corresponding to a porosity of 4.0%. As shown in Table 12, the optimal oil-stone ratio is 4.9%.

[0128] (7) Performance testing of recycled asphalt concrete with steel slag

[0129] Marshall specimens were prepared according to the gradation and optimal asphalt-aggregate ratio determined by the above steps. The Marshall stability, water immersion residual stability, low-temperature bending failure strain and dynamic stability of the concrete specimens were tested. The test results are shown in Table 13.

[0130] Table 13 Performance of Recycled Asphalt Concrete with Steel Slag

[0131]

[0132] As shown in Table 13, all performance requirements are met, and the mix proportion verification is qualified. Therefore, an asphalt-aggregate ratio of 4.9% is selected as the mix composition for the steel slag recycled asphalt concrete.

[0133] Example 3

[0134] (1) Determine the gradation and apparent relative density of steel slag.

[0135] Steel slag with a particle size of 4.75–13.2 mm was screened to obtain the slag gradation, i.e., the passing rate P of each sieve opening. gi The results are shown in Table 14. The apparent relative density γ1 of the steel slag was then determined using the basket method to be 3.204 g / cm³. 3 .

[0136] Table 14 Steel Slag Screening Results

[0137] <![CDATA[Pass rate P gi / %]]> 92.5 50.5 5.2

[0138] The above-mentioned basket method is the method provided by T0304-2005. The difference is that the water used in T0304-2005 is replaced with asphalt, the test temperature of the asphalt is 165℃, and the asphalt is No. 70 Grade A road petroleum asphalt.

[0139] (2) Determine the gradation of RAP

[0140] All recycled asphalt pavement RAP was crushed in a crusher to obtain waste asphalt mixture with a particle size ≤10mm. The crushed RAP was then evenly divided into two parts. One part was dried at 60-70℃ to constant weight and then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture.ai Another sample was processed using the combustion furnace method (the method provided in T0735-2011) to obtain the burned RAP and the asphalt content B1 = 7.0% in the RAP. The burned RAP was then sieved to obtain its gradation, i.e., the passing rate P of each sieve aperture. bi Using formula P Ri =θP ai +(1-θ)P bi With θ = 0.3, the corrected gradation of RAP is obtained, which is the throughput P per sieve aperture. i (See Table 15).

[0141] Table 15 RAP's Modified Gradation

[0142]

[0143] (3) Determine the aggregate gradation of recycled asphalt concrete with steel slag

[0144] The mineral powder is sieved to obtain its gradation, i.e., the passing rate P of each sieve opening. ki (See Table 16). Utilizing steel slag gradation P gi , RAP gradation P i And the gradation of mineral powder P ki Using the gradation range provided in Table 5.3.2-2 of JTG F40-2004 "Technical Specification for Construction of Asphalt Pavement on Highways" as a reference gradation range, a synthetic gradation was fitted. This resulted in the synthetic aggregate gradation P after steel slag, RAP, and mineral powder were mixed in different mass proportions. Hi (See Table 17) Within the reference gradation range, the mass ratios of steel slag, RAP, and mineral powder are A = 56%, B = 40%, and C = 4%. Among them, the mass of RAP is the mass of RAP without bitumen, that is, the mass of RAP multiplied by (1-B1), and B1 is the bitumen content in RAP measured in step (2).

[0145] Table 16. Gradation of mineral powder

[0146] <![CDATA[Pass rate P ki / %]]> 100 99.1 86.3

[0147] Table 17 Aggregate gradation of recycled asphalt concrete with steel slag

[0148]

[0149] (4) Determine the asphalt-aggregate ratio of the asphalt mixture.

[0150] Using the aggregate gradation determined in step (3), four asphalt-aggregate ratios of 4.4%, 4.6%, 4.8%, 5.0%, and 5.2% were designed at intervals of 0.2%. The asphalt included asphalt in RAP and added No. 70 Grade A road petroleum asphalt.

[0151] (5) Determine the maximum theoretical relative density of recycled asphalt concrete with steel slag.

[0152] The apparent relative density γ of the RAP after combustion in step (2) was measured using the methods provided in T0304-2005 and T0330-2005. sa =2.848g / cm 3 The relative volume density γ of RAP after combustion sb =2.777g / cm 3 and water absorption rate W x =0.9%, the effective relative density γ of RAP was calculated. se =2.826g / cm 3 The calculation formula is as follows:

[0153] C = 0.033W x 2 -0.2936W x +0.9339

[0154] γ se =C×γ sa +(1-C)×γ sb

[0155] In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x This represents the water absorption rate of RAP after combustion.

[0156] Based on the apparent relative density of steel slag γ1 = 3.204 g / cm³ 3 The effective relative density γ of RAP se =2.826g / cm 3 The relative density γ of mineral powder c= 2.691 g / cm³ 3 The relative density γ of asphalt a= 1.021g / cm 3 And the proposed oil-stone ratio P a The maximum theoretical relative density γ of recycled asphalt concrete with steel slag was calculated. ti The formula for calculating the maximum theoretical relative density of recycled asphalt concrete mixed with steel slag is:

[0157]

[0158] (6) Determine the porosity

[0159] Marshall tests were conducted based on the aggregate gradation and the proposed asphalt-aggregate ratio to determine the bulk density of Marshall specimens under different asphalt-aggregate ratios. Based on the maximum theoretical relative density of recycled asphalt concrete obtained in step (5), the porosity of the mixture under each asphalt-aggregate ratio was calculated. The relationship between the asphalt-aggregate ratio and porosity is shown in Table 18. The formula for calculating the porosity of the mixture is:

[0160]

[0161] In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. f The bulk density of the specimen is given.

[0162] Table 18 Relationship between oil-aggregate ratio and porosity

[0163] Porosity / % 5.2 4.5 4.1 3.8 3.2

[0164] The optimal oil-aggregate ratio is determined by interpolation based on a porosity of 4.0%. Table 18 shows that the optimal oil-aggregate ratio is 4.9%.

[0165] (7) Performance testing of recycled asphalt concrete with steel slag

[0166] Marshall specimens were prepared according to the gradation and optimal asphalt-aggregate ratio determined by the above steps. The Marshall stability, water immersion residual stability, low-temperature bending failure strain and dynamic stability of the concrete specimens were tested. The test results are shown in Table 19.

[0167] Table 19 Performance of Recycled Asphalt Concrete with Steel Slag

[0168]

[0169] As shown in Table 19, all performance requirements are met, and the mix proportion verification is qualified. Therefore, an asphalt-aggregate ratio of 4.9% is selected as the mix composition for the steel slag recycled asphalt concrete.

[0170] To better illustrate the technical effects of this invention, a comparative test of maximum theoretical relative density was conducted based on Example 3. Comparative Example 1 involved measuring the apparent relative density and bulk relative density of steel slag, while simultaneously treating the RAP as a whole and measuring its apparent density. The maximum theoretical relative density was then calculated according to the specifications in JTG F40-2004. The measured value was the maximum theoretical relative density obtained from the test of the asphalt mixture prepared in Example 3 according to the method in T0711-2011. The asphalt-aggregate ratio was 5.2% in all tests. The test results are shown in Table 20. The results show that the result calculated in Example 3 is closer to the measured value.

[0171] Table 20 Results of comparative experiments on maximum theoretical relative density

[0172] Maximum theoretical relative density <![CDATA[2.749g / cm 3 ]]> <![CDATA[2.618g / cm 3 ]]> <![CDATA[2.731g / cm 3 ]]>

[0173] Meanwhile, based on Example 3, a comparative test on the porosity of the mixture was conducted. The oil-aggregate ratio was 5.2% for all examples. The differences between Comparative Examples 2, 3, and 4 and Example 3 are: (1) the maximum theoretical relative density was measured using the method specified in T0711-2011; (2) the RAP in Comparative Examples 2, 3, and 4 was the RAP after combustion, measured according to the P in Table 15. i P bi and P ai The gradation was obtained through step-by-step sieving and fitting. The types and proportions of other mineral materials remained consistent. The deviation from Example 3 refers to the ratio of the absolute value of the difference between the porosity of a comparative example and the porosity of Example 3, expressed as a percentage, to the ratio of the absolute value of the difference between the porosity of a comparative example and Example 3. The results are shown in Table 21. The experimental results show that Example 3 and Comparative Example 2 have the smallest deviation, while Comparative Example 2 uses a corrected gradation, indicating that correcting the gradation of RAP yields more accurate results.

[0174] Table 21 Results of Porosity Comparison Test

[0175] porosity 3.2% 2.5% 2.0% 4.8% Deviation from Example 3 — 21% 38% 50%

[0176] It should be noted that all the above embodiments belong to the same inventive concept, and the descriptions of each embodiment have different focuses. Where the description in a particular embodiment is not detailed, please refer to the description in other embodiments.

[0177] The embodiments described above are merely illustrative of implementation methods of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A mix design method for recycled asphalt concrete with steel slag, characterized in that, Includes the following steps: S1. Utilize steel slag gradation, RAP gradation, and mineral powder gradation, combined with industry gradation range standards, to determine the aggregate gradation of recycled asphalt concrete with steel slag. S2. Determine the asphalt-aggregate ratio for recycled asphalt concrete with steel slag; S3. Based on the apparent relative density of steel slag, the effective relative density of RAP, the relative density of mineral powder, the relative density of asphalt, and the proposed asphalt-aggregate ratio, the maximum theoretical relative density of the steel slag-mixed recycled asphalt concrete is calculated; the formula for calculating the maximum theoretical relative density of the steel slag-mixed recycled asphalt concrete is as follows: In the formula, γ ti γ is the maximum theoretical relative density, γ1 is the apparent relative density of the steel slag, and γ se γ is the effective relative density of RAP. c γ represents the relative density of the mineral powder. a P is the relative density of the asphalt used. a The proposed oil-stone ratio; S4. Based on the aggregate gradation of the recycled asphalt concrete with steel slag and the proposed asphalt-aggregate ratio, Marshall tests were conducted to determine the bulk density of Marshall specimens under different asphalt-aggregate ratios. Based on the maximum theoretical relative density of the recycled asphalt concrete with steel slag, the porosity of the asphalt concrete with steel slag under each asphalt-aggregate ratio was calculated. S5. The optimal oil-stone ratio is the oil-stone ratio corresponding to a porosity of 4.0%. S6. Test the basic performance of recycled asphalt concrete with steel slag under the optimal asphalt-aggregate ratio and obtain the basic performance data. If the basic performance data meets the standard requirements, the optimal asphalt-aggregate ratio is used as the optimal mix proportion for the steel slag-infused recycled asphalt concrete. If the basic performance data does not meet the requirements, asphalt admixtures are added, and the basic performance is retested until the basic performance data meets the standard requirements. The optimal asphalt-aggregate ratio and the amount of asphalt admixture added are then used as the optimal mix proportion for the steel slag-infused recycled asphalt concrete.

2. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S1, the RAP gradation is a modified gradation of RAP, and the determination method includes: dividing the RAP evenly into two parts, drying one part to constant weight, and then sieving it to obtain the first gradation P. ai Another portion was subjected to combustion treatment, and the resulting RAP was sieved to obtain the second-grade P. bi Then use formula P Ri =θP ai +(1-θ)P bi The corrected gradation of RAP is obtained.

3. The mix design method for recycled asphalt concrete with added steel slag according to claim 2, characterized in that, The particle size of the RAP is ≤10mm; in the modified gradation calculation formula, the correction coefficient θ ranges from 0.1 to 0.

4.

4. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S3, the effective relative density of the RAP is determined as follows: the RAP is subjected to combustion treatment, and the effective relative density of the RAP is calculated based on the apparent relative density and the bulk relative density of the RAP after combustion. The formula for calculating the effective relative density of the RAP is as follows: C=0.033W x 2 -0.2936W x +0.9339 c se =C×γ sa +(1-C)×γ sb In the formula, γ se Where γ is the effective relative density of RAP, C is the bitumen absorption coefficient, and γ is the effective relative density of RAP. sa γ is the apparent relative density of RAP after combustion. sb W represents the bulk relative density of RAP after combustion. x The water absorption rate of RAP after combustion.

5. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S3, the apparent relative density of the steel slag is determined using the basket method.

6. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S2, the asphalt-aggregate ratio is the mass percentage of asphalt to aggregate, and the asphalt includes the asphalt in RAP and the asphalt to be added.

7. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S4, the formula for calculating the porosity of the steel slag-mixed asphalt concrete is as follows: In the formula, VV is the porosity, and γ is the porosity. ti γ is the maximum theoretical relative density of the specimen. f The bulk density of the specimen is given.

8. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S5, if there is no asphalt-aggregate ratio that exactly corresponds to a void ratio of 4.0%, it is determined by interpolation; if the void ratio of concrete corresponding to different asphalt-aggregate ratios does not cover 4.0%, the range of asphalt-aggregate ratios proposed in step S2 is expanded until the void ratio of concrete covers 4.0%.

9. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S6, the asphalt admixture includes one or more of petroleum resin, aromatic oil, SBS, and epoxy resin, and the dosage is 1 to 9% of the mass of asphalt in the steel slag recycled asphalt concrete.

10. The mix design method for recycled asphalt concrete with steel slag as described in claim 1, characterized in that, In step S6, the basic performance data includes Marshall stability, water immersion residual stability, low-temperature bending failure strain, and dynamic stability data.

Citation Information

Patent Citations

  • Composition of skeleton interlocking coarse grain-type high-modulus asphalt concrete and determination method thereof

    CN102503244A

  • Steel slag asphalt concrete mix proportion design method

    CN114249556A